Facilitators or suppressors: Effects of experimentally induced emotions on multimedia learning. (August 2016) - Knörzer, Lisa; Brünken, Roland; Park, Babette
Abstract: The present study investigated the influence of experimentally induced emotions (positive, neutral, negative) on learning with multimedia instruction with N = 75 university students. In order to provide sound explanations about how emotional state might impact learning, measures of motivation, cognitive load, and attentional processes (eye tracking) were integrated. Results showed that while emotions did not influence retention, emotions did influence outcomes of the comprehension and transfer test. Specifically, a facilitating effect of an induced negative emotional state on learning outcomes was observed, which could be attributed to a more focused and detailed information processing. In contrast, an induced positive emotional state had a suppressing effect on learning outcomes since learners were distracted from the learning materials by their emotions. Motivational measures were not influenced by learners' different emotional states, but overall, controlled motivation increased and autonomous motivation decreased during learning. In sum, the learners' emotional state should be considered in learning research as an important predictor for learning success. Highlights: The study investigated how emotions influence multimedia learning. Possible intervening mechanisms of action are introduced and examined. N = 75 participants received a positive, neutral or negative emotion induction. Positive emotions distracted from learning and suppressed learning outcomes. Negative emotions facilitated learning and more focused information processing.